Abruptness as a methaphisical inclination of being - Bańka, Józef (Folia Philosophica, 2001)
The core of the author’s considerations refers to the theory of recentivism developed by him. However, in the version of this philosophical direction presented here he introduces the new category of "abruptness" (Latin: subitum entis). Recentivism ascribes to nature the ontological tendency (the author uses the word “inclination”) to disrupt the continuity of phenomena and hide the essence of things in an emergency case. On this background recentivism proposes a new method of philosophising, a new type of reflection on man - the so called “rarity anthropology”. The author call abruptness a Rarity, or a world "created for one time”. Abruptness is the ability of reality to come to being only in the present and only for one moment. In this understanding events do not last, they do not produce conti nuity. The author analyses the consequences of accepting such a point of departure for the development of the theory of recentivism.